2015
DOI: 10.1002/anie.201501015
|View full text |Cite
|
Sign up to set email alerts
|

SBA‐15‐Oxynitrides as a Solid‐Base Catalyst: Effect of Nitridation Temperature on Catalytic Activity

Abstract: Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Herein, we design a nitrogen‐doped mesoporous carbon (NMC), prepared by a hard templating method using Zr‐SBA‐15 as the template and carbonized under a flow of ammonia for nitridation. This doping method results in a relatively clean substrate surface compared to doping with organic nitrogen sources . Furthermore, it is efficient for obtaining different nitrogen contents by altering the nitridation temperature.…”
Section: Hydrogenation Of Bicarbonate By Palladium‐based Catalysts[a]mentioning
confidence: 99%
“…Herein, we design a nitrogen‐doped mesoporous carbon (NMC), prepared by a hard templating method using Zr‐SBA‐15 as the template and carbonized under a flow of ammonia for nitridation. This doping method results in a relatively clean substrate surface compared to doping with organic nitrogen sources . Furthermore, it is efficient for obtaining different nitrogen contents by altering the nitridation temperature.…”
Section: Hydrogenation Of Bicarbonate By Palladium‐based Catalysts[a]mentioning
confidence: 99%
“…[138] Lately,t he scope of nitrogen-modified silica materials was expanded and oxynitride-like materials supported on KCC-1, SBA-15, and MCM-48 werep repared and used in Knoevenagel condensation reactions. [137,139,140] Recently,i tw as shown that the incorporation of polycationic nodes (Al 3 + ,C u 2 + ,A g 2 + ,F e 3 + ,R h 3 + ,M n 2 + ,Z r 2 + )i nto MOFs led to enhanced catalytic activity in selectiveoxidation, olefination, epoxidation,K noevenagelc ondensation, and so forth. [141] As an example, in one study, [142] aM OF consisting of Zn 5 Cl 4 (btdd) 3 (H 2 btdd = bis(1H-1,2,3-triazolo[4,5-b][4',5'-i])dibenzo [1,4]dioxin)) (MFU-4L) was investigated.I fc ertain Zn atoms weres ubstituted by Ti III ,T i IV ,C r II ,a nd Cr III atoms, MOFs with M x Zn 5Àx Cl 4 (btdd) 3 blocks were synthesized.T he formed MOFs were tested in ethylene polymerization;i tw as found that these MOFs produced high-molecular-weight, high-density polyethylene, which demonstrated morphological control over the polymer product by changingt he composition of the blocks in the MOF.…”
Section: Zeolites Mofs Cofs and Pops As Catalysts/catalyst Supportsmentioning
confidence: 99%
“…Although the procedure looked excellent for converting biomass‐derived molecules, it suffered from limitations such as substrate scope and recyclability. We have recently observed that the morphology of the support has dramatic effects on its catalytic activity: multifold enhancement of nitridated base‐catalyzed Knoevenagel condensations and trans ‐esterification reactions were observed when replacing the solid support from conventional silica, such as SBA‐15, with fibrous nanosilica, KCC‐1 …”
Section: Figurementioning
confidence: 99%
“…[35] Decarbonylation of biomass-derived molecules, such as 5-hydroxymethylfurfural and furfural, was achieved with palladium nanoparticles (PdNPs) that were impregnated on mesoporous silica support SBA-15 to provide furfuryl alcohol and furan, respectively.A lthough the procedure lookede xcellent for converting biomass-derived molecules, it suffered from limitations such as substrate scope and recyclability.W e have recently observed that the morphology of the support has dramatic effects on its catalytic activity:m ultifold enhancement of nitridated base-catalyzed Knoevenagel condensations and trans-esterification reactions were observed when replacing the solid support from conventional silica, such as SBA-15, with fibrous nanosilica, KCC-1. [36,37] Owing to its immense importance in chemistry,i ncluding the synthesis of natural products, [38,39] there is an eed to develop an environmentally benign decarbonylation method. The protocolise xpected to show substrate scopes similartot ransition-metal-catalyzed homogeneous reactions,a long with acceptable catalystr ecyclability and efficiency similar to heterogeneous reactions and preferentiallye asy product separation withoute xtra purification steps.…”
mentioning
confidence: 99%